Уплотнение сплавов Сu-Sn, Ni-Sn и Fe- Sn,полученных спеканием с последующим прессованием с использованием их в породоразрушающем инструменте - Бондаренко, Н.А.; Мечник, В.А.; Супрун, М.В.; Дутка, В.А.; Коростышевский, Д.Л. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
It is studied shrinkage kinetics at sintering of binary systems Cu-Sn, Ni-Sn and Fe-Sn in a usual muffle furnace with the subsequent pressing. The reasons of change of velocity of shrinkage are discussed at sintering of the samples gained on the basis of these systems, under various requirements. It is shown, that the activation energy and the kinetic parameters characterize the key moments of the given process.